The metabotropic glutamate receptor 2/3 antagonist LY341495 improves working memory in adult mice following juvenile social isolation. (15th October 2020) - Zhang, Xiao-Qin; Jiang, He-Jia; Xu, Le; Yang, Si-Yu; Wang, Gao-Zhe; Jiang, Hong-De; Wu, Teng; Du, Han; Yu, Zhi-Peng; Zhao, Qi-Qi; Ling, Yu; Zhang, Zhong-Yu; et al.
Abstract: Juvenile social isolation (SI) and neglect have a negative impact on neurodevelopment persistently, which is associated with cognitive dysfunction in neurodevelopmental disorders. Given the critical role of metabotropic glutamate receptors (mGluRs) in synaptic homeostasis of the prefrontal cortex (PFC), pharmacological intervention on mGluRs has been attempted in order to improve cognitive dysfunction in animal models of neurodevelopmental disorder, as well as in clinical trials. Here we examined the effects of the mGluR2/3 antagonist LY341495 on prefrontal synaptic transmission, spatial working memory, and recognition memory in adult C57BL/6J mice that experienced juvenile SI. We found that SI-reared mice exhibited working memory impairment and decreased excitatory presynaptic release probability of pyramidal neurons in the medial PFC compared with group-reared mice. The positive effect of LY341495 on excitatory synaptic transmission in SI-reared mice was more prominent than the effect in group-reared mice. A single treatment with mGluR2/3 antagonist LY341495 significantly improved the performance of SI-reared mice in the Y-maze test but not in the novel object recognition (NOR) test, while repeated treatments were effective in both tasks. These findings suggest that enhancing glutamatergic transmission via inhibition of mGluR2/3 signaling might represent a promising strategy for improving cognitive function in neurodevelopmental disorders. Highlights: Juvenile social isolation induced cognitive deficits in adulthood. Decreased excitatory presynaptic release probability of pyramidal neurons in the mPFC of socially isolated mice. The effect of LY341495 on presynaptic regulation was more prominent in socially isolated mice. LY341495 improved working memory with relatively high synaptic strength in the mPFC of socially isolated mice.